Faktor-faktor Minat Belajar Siswa menggunakan Model Blended Learning Selama Kegiatan Pembelajaran Jarak Jauh - Fadjriah Hapsari; Mirna Herawati; Dhona Shahreza (Journal on Education, 2023)
The purpose of this study is to describe how blended learning can be used to increase students' interest in learning. Blended Learning is an application created to address the limitations between educators and students, specifically in terms of space and time. Motivation to learn is a psychological aspect that manifests itself in some symptoms, such as; passion, desire, feelings of liking to change behavior through various activities that include seeking knowledge and experience. This research uses a qualitative descriptive approach with a phenomenological approach, namely describing or portraying research objects based on facts that are visible or as they are. The research results show that learning can be done online using blended learning, so it is necessary to give full attention in learning and the existence of such attention because students are happy and challenged to follow the learning activities in class and in the classroom. The level of interest that students have in learning is affected by both internal and external factors. Students who are physically and mentally capable, and who have supportive learning environments, are more likely to be interested in learning. The use of blended learning methods is very helpful in learning during times of pandemics like the present, as it can help spark children's interest in learning and keep them motivated.